A polymorphism of the CREB binding protein (CREBBP) gene is a risk factor for addiction - Kumar, Deepak; Deb, Ishani; Chakraborty, Japashish; Mukhopadhyay, Sikha; Das, Sumantra (Brain research, 2011)
Unequivocal evidences have implicated c-AMP response element binding protein (CREB) in drug addiction. Recent reports indicate that the CREB binding protein (CREBBP), a transcription co-activator, may also be involved in the sensitivity to drugs of abuse. We undertook studies on the single nucleotide polymorphisms (SNP) at selective areas of CREBBP gene in heroin as well as in alcohol addicts and compared them with that in normal population. One hundred fifty healthy controls, one hundred thirty heroin addict and one hundred ten alcohol addicts, all males, Bengali-Hindu, and residing in Kolkata, a city in eastern India, participated in the study. DNA prepared from blood drawn from the subjects was PCR amplified for the regions corresponding to exon 3 and 22 of CREBBP gene followed by sequencing. Three SNPs identified in the population were analyzed to find out the association of these SNPs with addiction. One SNP, rs3025684 in intron 21 having the contig position of 3795363, showed association with addiction. The genotype frequencies of the SNP were significantly different between opioid dependent cases and controls ( χ 2 = 20.28, p < 0.0001) as well as between alcoholics and controls ( χ 2 = 13.60, p = 0.0011). Our studies suggest that rs3025684 polymorphism may be a possible risk factor for developing addiction. ► Distribution of SNPs at selective areas of CREBBP gene have been studied. ► Subjects include narcotic and alcohol addicts and normal volunteers. ► Three SNPs, two reported and one novel have been identified in the population. ► One SNP, rs 3025684 in intron 21 showed association with addiction.